TLR7 controls myeloid-derived suppressor cells expansion and function in the lung of C57BL6 mice infected with Schistosoma japonicum - Lu Zhou; Yiqiang Zhu; lengshan Mo; Mei Wang; Jie Lin; Yi Zhao; Yuanfa Feng; Anqi Xie; Haixia Wei; Huaina Qiu; Jun Huang; Quan Yang (Public Library of Science (PLoS), 2022)
Toll-like receptors (TLRs) play an important role in the induction of innate and adaptive immune responses against Schistosoma japonicum (S. japonicum) infection. However, the role of Toll-like receptor 7 (TLR7) in the mouse lung during S. japonicum infection and the myeloid-derived suppressor cells (MDSCs) affected by the absence of TLR7 are not clearly understood. In this study, the results indicated that the MDSCs were accumulated and the proportion and activation of CD4+ and CD8+ T cells were decreased in the lung of mice at 6-7 weeks after S. japonicum infection. Then, the expression of TLR7 was detected in isolated pulmonary MDSCs and the results showed that the expression of TLR7 in MDSCs was increased after infection. Furthermore, TLR7 agonist R848 could down-regulate the induction effect of the soluble egg antigen (SEA) on pulmonary MDSCs in vitro. Meanwhile, TLR7 deficiency could promote the pulmonary MDSCs expansion and function by up-regulating the expression of PD-L1/2 and secreting of IL-10 in the mice infected with S. japonicum. Mechanistic studies revealed that S. japonicum infection and the antigen effects are mediated by NF-κB signaling. Moreover, TLR7 deficiency aggravates S. japonicum infection-induced damage in the lung, with more inflammatory cells infiltration, interstitial dilatation and granuloma in the tissue. In summary, this study indicated that TLR7 signaling inhibits the accumulation and function of MDSCs in S. japonicum infected mouse lung by down-regulating the expression of PD-L1/2 and secreting of IL-10, via NF-κB signaling. Author summary Schistosomiasis is a zoonotic parasitic disease that seriously affects human health. Many adults and children with schistosomiasis develop lung symptoms such as coughing, chest pain and bloody sputum. In addition to their respiratory and metabolic functions, the lungs also play a role in the immune system. MDSCs play an important role in Schistosoma infection-induced diseases. TLR7 is an intracellular member of the innate immune receptor. The role of TLR7 on MDSCs mediated immune response in the lung is still unclear. Here, our data showed that the percentage and numbers of MDSCs increased in the lung of infected mice, and the expression of TLR7 in pulmonary MDSCs was increased after infection. When TLR7 gene was knockout, the percentage of pulmonary MDSCs was increased after infection and the expression of PD-L1/2 and IL-10 were increased in S. japonicum infection-induced pulmonary MDSCs. Additionally, the effects of TLR7 on pulmonary MDSCs are dependent on the activation of NF-κB p65. Finally, we found TLR7 deficiency aggravates S. japonicum infection-induced damage in the lung, with more interstitial dilatation, thickened alveolar cavity and granuloma. In this study, the characteristic of MDSCs in the lung of S. japonicum infected C57BL/6 mice was explored, and the role of TLR7 on the progress of MDSCs activation and differentiation was investigated.